2009
DOI: 10.1111/j.1600-0897.2009.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Expression of Autotaxin, an Ectoenzyme that Produces Lysophosphatidic Acid, in Human Placenta

Abstract: These findings suggest that trophoblasts might produce ATX and its bioactive resultant substance, LPA, paralleled with gestational weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…During pregnancy, ATX concentration is upregulated in the serum and placenta of healthy women in the third trimester. Interestingly, patients with pregnancyinduced hypertension (preeclampsia) harbored decreased ATX levels in the third trimester compared with healthy women (56,167,168). LPA receptors are also expressed in the testis (19,77,88), suggesting a role for LPA signaling in male sperm behavior and fertility.…”
Section: Lpamentioning
confidence: 99%
“…During pregnancy, ATX concentration is upregulated in the serum and placenta of healthy women in the third trimester. Interestingly, patients with pregnancyinduced hypertension (preeclampsia) harbored decreased ATX levels in the third trimester compared with healthy women (56,167,168). LPA receptors are also expressed in the testis (19,77,88), suggesting a role for LPA signaling in male sperm behavior and fertility.…”
Section: Lpamentioning
confidence: 99%
“…Interestingly, although increased expression of ATX has been associated with increased cancer progression, ATX antigen levels in serum were not increased in ovarian cancer patients when compared to healthy controls [64]. Furthermore, ATX may not be useful as a diagnostic marker for ovarian cancer, as ATX is also elevated in other conditions, including liver disease, acute coronary syndrome and pregnancy [6567]. …”
Section: Lipidsmentioning
confidence: 99%
“…The elevated serum ATX antigen level decreased after delivery to near the level observed in nonpregnant women. A recent immunohistochemical study showed that ATX is expressed in placental tissues, especially trophoblasts, and the ATX mRNA level in placental tissues increased in parallel with the gestational week (63). Together with the observation that the serum ATX antigen level decreased immediately after delivery, it seems likely that ATX is produced in placental trophoblasts during pregnancy (Fig.…”
Section: Serum Atx Measurements In Pregnant Womenmentioning
confidence: 92%
“…Although the details of ATX biosynthesis and regulation of the serum ATX level in physiological states remain largely unknown, we feel that the level of ATX may be maintained by its release from adipose tissue based upon previous studies (38,39). Furthermore, in pregnancy, the serum ATX level is enhanced possibly because of its synthesis in the placenta (63).…”
Section: The Usefulness Of Serum Atx Measurement In Laboratory Medicinementioning
confidence: 99%